Analysis of the July 10th 2013 Tectonic Earthquake effect on the Coordinates Changes of Mentawai Segment Monitoring Station - Hilmiyati Ulinnuha; Aris Sunantyo; Nurrohmat Widjajanti (Jurnal Geospasial Indonesia, 2019)
Mentawai Segment is located in Mentawai Islands, Sumatra, Indonesia. This segment is a subduction zone between Indo-Australian plate and Eurasian plate. This subduction zone can lead to high potential of tectonic earthquake in Mentawai Segment. The high potential of tectonic earthquake has negative impact for the community, so it is necessary to monitor the risk of tectonic earthquake in Mentawai Segment. This monitoring can be done by using GPS data of monitoring station that spread in Mentawai Segment. Therefore, this research aims to analyze the effect of tectonic earthquake on the coordinate change of Mentawai Segment, so that it can reduce the risk of negative impact of tectonic earthquake in Mentawai Segment. This research use observation data of 10 continuous GPS monitoring station (Sumatran GPS Data Array / SuGAr) in Mentawai Segment. Day of observation data was day of year (doy) at the time of tectonic earthquake occurence on July 10, 2013. Data processing used GAMIT / GLOBK software. The results of this research indicate that the tectonic earthquake (July 10, 2013) affected coordinates changes of the SuGAr station significantly two hours after the tectonic earthquake occurred.